Removal of heavy metals from electroplating wastewater using bacteria - Mustapha, Mohammed Umar (2016)
Pollution of water bodies by industrial discharges containing toxic chemicals are one of the major areas of concern globally. Heavy metal ions cause human health and ecological risk because they usually form compounds that can be poisonous, carcinogenic or mutagenic even in small concentrations. Heavy metals used for electroplating are copper, chromium, nickel, lead, cadmium, tin, zinc, brass or combinations of them. Platers immerse objects into a series of chemical baths in order to improve their surface conditions. Electroplating wastewater is typically from washing, rinsing and batch dumps and is usually at a very low pH of 2-5 and contains soluble forms of the various metals. Many conventional methods for treating wastewater containing metals have some technical constrain. The purposes of the study were to screen, isolate, and identify bacteria resistant to heavy metals, to be used in metals bioaccumulation studies. Isolation of single colonies of bacteria was conducted using series of dilution and spread plate method. The selected isolates were partially identified using biochemical tests and molecular technique by isolating the genomic DNA and amplification using Polymerase Chain Reaction (PCR). Optimization studies were performed to determine the optimum growth condition of the bacteria. Minimum inhibitory concentrations (MIC) of each isolate were determined in Luria Bertani (LB) Agar medium with metals chromium, copper, cadmium and lead concentrations from 50-200 mg/L. The bacteria were tested in the presence of individual metals for their growth studies. Bioaccumulation experiments were also performed with the living biomasses of Bacillus sp. and Ochrobactrum sp. under different pH (5, 7, and 9) and temperature (27 ºC, 32ºC and 37 ºC) with biomass free solution used as control. The environmental factors such as pH and temperature affected the bioaccumulation capacity tremendously. Scanning Electron Microscopy (SEM) and Energy disperse X-ray (EDX) were used to examine the bacterium cells before and after exposure to metal ions. Results from the present study shows that twenty one (21) bacterial single colonies were screened and five isolates resistant to cadmium, chromium, copper and lead were chosen after numerous round of culture and were named MH1, MH4, MH6, MH15 and MH21. Results from the optimization shows that 37°C was the optimum temperature for the growth of the bacteria and pH 7.0 was also the optimum pH for their growth. The ii examination of the bacteria using 16s rRNA gene sequencing analysis shows ten main taxonomic lineages. The bacteria MH15 and MH6 were identified as Bacillus sp. and Ochrobactrum sp.. The selected bacteria responded positively to the medium supplemented with up to 200 mg/L of metals by showing an extended lag phase. Growth studies of the bacteria show that they are able to survive the increasing concentrations of heavy metals. The results from the bioaccumulation experiments shows that the biomass of Ochrobactrum sp. shows better bioaccumulation capacity to Cu2+ ion up to 79.9%. While, chromium was removed more efficiently by living cells of Bacillus sp. than Ochrobactrum sp. biomass. The maximum chromium removal by bacillus sp. was 49.7 %. There was significant difference (P≤ 0.05) between temperature, pH and time in copper removal studies. Based on the results, the selected bacterial strains performed differently under different environmental conditions. Therefore, they could be used for heavy metals removal in different environments where the pH and temperature is closer to their optimum conditions. SEM and EDX of metals treated and untreated results show that there were visible changes in the bacterial cells morphology before and after bioaccumulation studies, revealing that the metals were accumulated on the cells of the bacteria.